2021
DOI: 10.1186/s12894-021-00831-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors of bladder neck contracture following transurethral surgery of prostate

Abstract: Backgrounds The aim of the present study was to investigate the perioperative parameters associated with bladder neck contracture (BNC) after transurethral surgery of the prostate and to compare the incidence of BNC after transurethral resection of the prostate (TURP) or Thulium vaporesection (resection group) versus Thulium vapoenucleation or enucleation of the prostate (enucleation group). Methods Between March 2008 and March 2020, 2363 patients … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 19 publications
2
5
1
Order By: Relevance
“…Our urethrotomy incidence is similar to the study of Sucki et al (21) and is within the lower range of the 1.4-19% referred in literature (3,20). Our BNC is relatively lower than the 1.7-9.7% mentioned in other studies (20,22,23). We only considered surgical reintervention made in our centre or another one of the Portuguese National Health Service, therefore, there is a chance that some patients who have had surgical reintervention in private clinical setting could be missed.…”
Section: Resultssupporting
confidence: 91%
“…Our urethrotomy incidence is similar to the study of Sucki et al (21) and is within the lower range of the 1.4-19% referred in literature (3,20). Our BNC is relatively lower than the 1.7-9.7% mentioned in other studies (20,22,23). We only considered surgical reintervention made in our centre or another one of the Portuguese National Health Service, therefore, there is a chance that some patients who have had surgical reintervention in private clinical setting could be missed.…”
Section: Resultssupporting
confidence: 91%
“…We found smaller preoperative prostate volume to be an independent risk factor for postoperative BNC formation. This is in accordance with most of the literature on this topic, which suggests that the ratio between prostate volume and resectoscope diameter contributes significantly to BNC formation 4,8,10–12 …”
Section: Discussionsupporting
confidence: 91%
“…Sun et al showed in a randomized trial that the incidence of BNS in men with small prostate (volume ≤ 30 g) was significantly higher in those who underwent resection with Thulium laser (13.6%) compared with those who underwent enucleation with Thulium laser (1.8%, p = 0.045) (Sun et al, 2019). Chen et al confirmed that small prostates and shorter surgical time were predictors of BNS after ThuLEP and demonstrated that a prostate volume <42.9 cm 3 had 76.6% sensitivity and 40.9% specificity in predicting BNS (Chen et al, 2021). In our study, men suffering from BNS had significantly smaller prostate (median volume 43.5 ml) compared with those with no BNS (median volume 66.0 ml, p = 0.008).…”
Section: Discussionmentioning
confidence: 98%
“…There might be also other factors that may contribute to the development of the US, such as prostate volume, and duration of surgery. Studies aiming to evaluate risk factors for lower urinary tract stenosis following transurethral surgery for BPH are currently limited (Chen et al, 2021; Garza‐Montúfar et al, 2021; Tao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%